2021
DOI: 10.1680/jmacr.19.00485
|View full text |Cite
|
Sign up to set email alerts
|

Concrete with rejected recyclable plastic waste at high temperatures

Abstract: The physical, chemical and mechanical properties of concrete incorporating rejected recyclable plastic waste (RRPW), the potential for the mitigation of heat-induced concrete spalling and the effects of high temperature on the residual properties of concrete were investigated. Concrete compressive and tensile strengths, Young's modulus, crack width, mass loss, water absorption by capillarity, chemical composition and evidence of heat-induced concrete spalling were monitored in concrete samples made with RRPW p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…CPW samples showed lower absorption by capillarity when compared to CREF after heating, which could be related to the surface morphology of the plastic waste and potentially less internal damage caused by the exposure to high temperature [ 1 , 68 ]. Ozawa and Marimoto [ 39 ] reported that the morphology of the polymeric addition might help to prevent the development of high vapor pressures within the concrete.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CPW samples showed lower absorption by capillarity when compared to CREF after heating, which could be related to the surface morphology of the plastic waste and potentially less internal damage caused by the exposure to high temperature [ 1 , 68 ]. Ozawa and Marimoto [ 39 ] reported that the morphology of the polymeric addition might help to prevent the development of high vapor pressures within the concrete.…”
Section: Resultsmentioning
confidence: 99%
“…The growing public concern on excessive plastic waste generation and poor final disposal results in global commitments to the production of recyclable, reusable, or compostable industrial products [ 1 ]. On the other hand, although technically recyclable, most types of plastic packaging are economically impossible to recycle and are expected to remain so for the foreseeable future [ 2 ], which induces product manufacturers to use new high-quality plastic bought at a lower cost [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Camilo et al [19] in their work, investigated the impacts of high temperature on the residual qualities of concrete, as well as the physical, chemical, and mechanical properties of concrete comprising rejected recyclable plastic waste (RRPW), were explored. After 2 hours of exposure to 200°C, 400°C, and 600°C, concrete compressive and tensile strengths, Young's modulus, crack width, mass loss, water absorption by capillarity, chemical composition, and evidence of heat-induced concrete spalling were measured in concrete samples made with RRPW particles and compared to those made with commercial polypropylene (PP) fibres.…”
Section: Literature Surveymentioning
confidence: 99%
“…From the survey, for [19] issues with workability and durability when using RRPW in high-strength concrete, for [20] more development on green materials is required for a sustainable environment and to minimize gas emissions, for [21] analysis of spalling for various structures has not concentrated, for [10] the spalling effect of the plastic aggregate induced concrete for beam structures and other structural members has to be analyzed and for [22] spalling effect of the specimens due to increased thermal gradients. Hence as a result to overcome the issues in spalling effect of reinforced plastic wastes has to be experimentally investigated.…”
Section: Literature Surveymentioning
confidence: 99%
“…On the other hand, recycled plastic wastes can also improve selected properties of cement-based material, e.g. reduce its plastic shrinkage [10] or enhance the performance in fire [11] , [12] . The latter case is possible due to the decomposition of polypropylene, which is a common compound of plastic wastes, beginning around 200°C.…”
Section: Introductionmentioning
confidence: 99%